Development of FAQ Chatbot for Digitization of Warung Gungbiang Marketing in Bali - Anak Agung Sandatya Widhiyanti; I Gusti Agung Ayu Sekarini (Eduvest - Journal of Universal Studies, 2025)
This research aims to develop a chatbot based on frequently ask question to support more modern digital marketing strategies. Research methods include problem identification, interviews, observation, literature study, designing, developing and testing chatbots. The chatbot was designed using a rule-based approach and developed with PHP and JavaScript technology. Testing involves Blackbox methods to ensure functionality and User Acceptance Testing (UAT) with a Likert scale to evaluate user satisfaction. Blackbox testing shows that the chatbot functionality has succeeded in providing fast and accurate responses to various customer questions regarding products, prices and ordering methods, while in UAT testing, the design, service and efficiency aspects of the chatbot received a score of "very good" with an average percentage above 80%. The implementation of this chatbot is able to increase information accessibility and customer convenience, while also supporting the digitalization of Warung Gungbiang's marketing.